Comportamiento alimentario de “sajino” Pecari tajacu en semicautiverio del zoocriadero, UNAP, Loreto, Perú - Del Aguila Yaicate, Francisco (2023)
Understanding the behavior of animals is of great importance to improve their welfare when handling. For this reason, the objective of the study was to know the feeding behaviors of "peccary" Pecari tajacu in semi-captivity at the Zoocriadero, UNAP, Loreto, Peru, from February to November of the year 2021. Fifteen Pecari tajacu born in captivity and introduced to the environment were studied. of semi-captivity. The data was obtained through the ethological techniques of Ad Libitum and Scan Sampling, from 5:00 am to 6:00 pm. Totaling five hundred and seventy-two hours of observation. 32 behaviors grouped into 8 categories were identified. The most frequent behaviors being: Eat while standing (19.7%), Sniff (19.4%), Articulate the front legs and lick the ground (6.13%), Explore in a group (6%), Hoza (4.6%), Eat while walking (4.4%), Drinking water from the drinking fountain (4.2%), chewing hard (3.6%); the other behaviors oscillate between 2.8% and 0.03. Regarding the types of food with the greatest preference, it is fruit (41.3%), leaf (33.8), flower (9.2), root (8.1), stem (6.2), the other items fluctuate between 0.6% and 0.3%. In relation to the frequency of feeding, this species is more active feeding in the early hours of the day, being less active between 10 and 12 of the day and moderately active from 15 to 18 hours. It is concluded that Pecari tajacu in semi-captivity presents varied behaviors and eating items, spending between ten and eleven hours a day performing eating behaviors, which is essential to improve the management of this species.